The sciences good study guide - Northedge, Andrew (Milton Keynes : Open University, 2002)
A guide which will help any student in the study of Science. Information on observations and experimenting, different modes of science writing and completing assignments, and importantly, on tackling examinations.
First published 1997.
Reprinted 1997, 1998, 2000, 2002.
Includes bibliographical references and index.
Keywords: Study skills